Developing Qur'anic Communication Corpus "MGG&&Tf Qur'CC INNOVA" For Pedagogical Delivery - Asma Abdul Rahman; Nurkhamimi Zainuddin; Puziah Abd. Wahab; Ahmad Abdul Rahman (International Journal of Latest Research in Humanities and Social Science, 2024)
International Journal of Latest Research in Humanities and Social Science (IJLRHSS) Volume 02 - Issue 06, 2019 www.ijlrhss.com || PP. 43-47